Growth and accumulation of nitrogen by sugarcane cultivated in soil covered with cane trash - Gava, Glauber José de Castro; Trivelin, Paulo Cesar Ocheuze; Oliveira, Mauro Wagner de; Penatti, Claudimir Pedro (Pesquisa Agropecuaria Brasileira, 2001)
The experiment was carried out to evaluate the use of nitrogen from urea and the influence of the cane trash in the productivity of sugarcane ratoon. It was a field experiment, in a ustalfs soil, in Piracicaba, SP, Brazil, in October 1997, with two treatments: application of a vinasse-urea mixture in the total area of a soil covered with cane trash; and urea buried in furrows in both sides of the cane rows, with previous application of vinasse in a soil without cane trash. A randomized block design with four replications was used. Parameters of crop productivity accumulation of N by the top and use of urea N by the crop were evaluated in each treatment. Plant development was represented by a dry matter mass accumulation and by physiological indexes of dry matter production rate and relative growth rate, which were similar in both conditions, with and without cane trash. From the total N accumulated in the top of the sugarcane ratoon, 10-16% was absorbed from the fertilizer. The mean efficiency of the use of urea N by the sugarcane ratoon was 17%.